If a=(√5+2)/(√5-2) and b=(√5-2)/(√5+2) then find the value of a^2-b^2
Answers
Answered by
4
hey mate ur answer is here In this picture.
Attachments:
![](https://hi-static.z-dn.net/files/def/a90ef53ef968ef103594db37c32c8c19.jpg)
Answered by
12
Here's your answer !!
____________________________
It's given that,
![= > a = \frac{ \sqrt{5} + 2}{ \sqrt{5} - 2 } = > a = \frac{ \sqrt{5} + 2}{ \sqrt{5} - 2 }](https://tex.z-dn.net/?f=+%3D+%26gt%3B+a+%3D+%5Cfrac%7B+%5Csqrt%7B5%7D+%2B+2%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+)
We will now rationalise it ,
![= > \frac{ \sqrt{5} + 2 }{ \sqrt{5} - 2 } \times \frac{ \sqrt{5} + 2}{ \sqrt{5} + 2} = > \frac{ \sqrt{5} + 2 }{ \sqrt{5} - 2 } \times \frac{ \sqrt{5} + 2}{ \sqrt{5} + 2}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B+%5Csqrt%7B5%7D+%2B+2+%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+%5Ctimes+%5Cfrac%7B+%5Csqrt%7B5%7D+%2B+2%7D%7B+%5Csqrt%7B5%7D+%2B+2%7D+)
![= > \frac{ {( \sqrt{5} + 2) }^{2} }{( { \sqrt{5} )}^{2} - {(2)}^{2} } = > \frac{ {( \sqrt{5} + 2) }^{2} }{( { \sqrt{5} )}^{2} - {(2)}^{2} }](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B+%7B%28+%5Csqrt%7B5%7D+%2B+2%29+%7D%5E%7B2%7D+%7D%7B%28+%7B+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D+-+%7B%282%29%7D%5E%7B2%7D+%7D+)
![= > \frac{5 + 4 + 4 \sqrt{5} }{1} = > \frac{5 + 4 + 4 \sqrt{5} }{1}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B5+%2B+4+%2B+4+%5Csqrt%7B5%7D+%7D%7B1%7D+)
![a= 9 + 4 \sqrt{5} a= 9 + 4 \sqrt{5}](https://tex.z-dn.net/?f=+a%3D+9+%2B+4+%5Csqrt%7B5%7D+)
Now,
![b = \frac{ \sqrt{5} - 2}{ \sqrt{5} + 2 } b = \frac{ \sqrt{5} - 2}{ \sqrt{5} + 2 }](https://tex.z-dn.net/?f=b+%3D+%5Cfrac%7B+%5Csqrt%7B5%7D+-+2%7D%7B+%5Csqrt%7B5%7D+%2B+2+%7D+)
By rationalizing it,we get :-
![= > \frac{ \sqrt{5} - 2 }{ \sqrt{5} + 2 } \times \frac{ \sqrt{5} - 2}{ \sqrt{5} - 2 } = > \frac{ \sqrt{5} - 2 }{ \sqrt{5} + 2 } \times \frac{ \sqrt{5} - 2}{ \sqrt{5} - 2 }](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B+%5Csqrt%7B5%7D+-+2+%7D%7B+%5Csqrt%7B5%7D+%2B+2+%7D+%5Ctimes+%5Cfrac%7B+%5Csqrt%7B5%7D+-+2%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+)
![= > \frac{ {( \sqrt{5} - 2)}^{2} }{ {( \sqrt{5} )}^{2} - {(2)}^{2} } = > \frac{ {( \sqrt{5} - 2)}^{2} }{ {( \sqrt{5} )}^{2} - {(2)}^{2} }](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B+%7B%28+%5Csqrt%7B5%7D+-+2%29%7D%5E%7B2%7D+%7D%7B+%7B%28+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D+-+%7B%282%29%7D%5E%7B2%7D+%7D+)
![= > \frac{5 + 4 - 4 \sqrt{5} }{1} = > \frac{5 + 4 - 4 \sqrt{5} }{1}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7B5+%2B+4+-+4+%5Csqrt%7B5%7D+%7D%7B1%7D+)
![b= 9 - 4 \sqrt{5} b= 9 - 4 \sqrt{5}](https://tex.z-dn.net/?f=+b%3D+9+-+4+%5Csqrt%7B5%7D+)
We have to find value of ,
![= > {a}^{2} - {b}^{2} = > {a}^{2} - {b}^{2}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%7Ba%7D%5E%7B2%7D+-+%7Bb%7D%5E%7B2%7D+)
![= > {(9 + 4 \sqrt{5}) }^{2} - {(9 - 4 \sqrt{5} )}^{2} = > {(9 + 4 \sqrt{5}) }^{2} - {(9 - 4 \sqrt{5} )}^{2}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%7B%289+%2B+4+%5Csqrt%7B5%7D%29+%7D%5E%7B2%7D+-+%7B%289+-+4+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D+)
![= > (81 + 80 + 8 \sqrt{5} ) - (81 + 80 - 8 \sqrt{5} ) = > (81 + 80 + 8 \sqrt{5} ) - (81 + 80 - 8 \sqrt{5} )](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%2881+%2B+80+%2B+8+%5Csqrt%7B5%7D+%29+-+%2881+%2B+80+-+8+%5Csqrt%7B5%7D+%29)
![= > 81 + 80 + 8 \sqrt{5} - 81 - 80 + 8 \sqrt{5} = > 81 + 80 + 8 \sqrt{5} - 81 - 80 + 8 \sqrt{5}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+81+%2B+80+%2B+8+%5Csqrt%7B5%7D+-+81+-+80+%2B+8+%5Csqrt%7B5%7D+)
![81 \: and \: - 81 \: 80 \: and \: - 80 \:get \: cancelled 81 \: and \: - 81 \: 80 \: and \: - 80 \:get \: cancelled](https://tex.z-dn.net/?f=81+%5C%3A+and+%5C%3A+-+81+%5C%3A+80+%5C%3A+and+%5C%3A+-+80+%5C%3Aget+%5C%3A+cancelled)
![= > 16 \sqrt{5} = > 16 \sqrt{5}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+16+%5Csqrt%7B5%7D+)
Hence,
![= > {a}^{2} - {b}^{2} = 16 \sqrt{5} = > {a}^{2} - {b}^{2} = 16 \sqrt{5}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%7Ba%7D%5E%7B2%7D+-+%7Bb%7D%5E%7B2%7D+%3D+16+%5Csqrt%7B5%7D+)
______________________________
Hope it helps you!! :)
____________________________
It's given that,
We will now rationalise it ,
Now,
By rationalizing it,we get :-
We have to find value of ,
Hence,
______________________________
Hope it helps you!! :)
Answered by
11
Here's your answer !!
____________________________
It's given that,
![= > a = \frac{ \sqrt{5} + 2}{ \sqrt{5} - 2 } = > a = \frac{ \sqrt{5} + 2}{ \sqrt{5} - 2 }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+a+%3D++%5Cfrac%7B+%5Csqrt%7B5%7D++%2B+2%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+)
We will now rationalise it ,
![= > \frac{ \sqrt{5} + 2 }{ \sqrt{5} - 2 } \times \frac{ \sqrt{5} + 2}{ \sqrt{5} + 2} = > \frac{ \sqrt{5} + 2 }{ \sqrt{5} - 2 } \times \frac{ \sqrt{5} + 2}{ \sqrt{5} + 2}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B+%5Csqrt%7B5%7D+%2B+2+%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+++%5Ctimes++%5Cfrac%7B+%5Csqrt%7B5%7D+%2B+2%7D%7B+%5Csqrt%7B5%7D++%2B+2%7D+)
![= > \frac{ {( \sqrt{5} + 2) }^{2} }{( { \sqrt{5} )}^{2} - {(2)}^{2} } = > \frac{ {( \sqrt{5} + 2) }^{2} }{( { \sqrt{5} )}^{2} - {(2)}^{2} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B+%7B%28+%5Csqrt%7B5%7D+%2B+2%29+%7D%5E%7B2%7D+%7D%7B%28+%7B+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D++-++%7B%282%29%7D%5E%7B2%7D+%7D+)
![= > \frac{5 + 4 + 4 \sqrt{5} }{1} = > \frac{5 + 4 + 4 \sqrt{5} }{1}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B5+%2B+4+%2B+4+%5Csqrt%7B5%7D+%7D%7B1%7D+)
![a= 9 + 4 \sqrt{5} a= 9 + 4 \sqrt{5}](https://tex.z-dn.net/?f=+a%3D+++9+%2B+4+%5Csqrt%7B5%7D+)
Now,
![b = \frac{ \sqrt{5} - 2}{ \sqrt{5} + 2 } b = \frac{ \sqrt{5} - 2}{ \sqrt{5} + 2 }](https://tex.z-dn.net/?f=b+%3D++%5Cfrac%7B+%5Csqrt%7B5%7D++-+2%7D%7B+%5Csqrt%7B5%7D+%2B+2+%7D+)
By rationalizing it,we get :-
![= > \frac{ \sqrt{5} - 2 }{ \sqrt{5} + 2 } \times \frac{ \sqrt{5} - 2}{ \sqrt{5} - 2 } = > \frac{ \sqrt{5} - 2 }{ \sqrt{5} + 2 } \times \frac{ \sqrt{5} - 2}{ \sqrt{5} - 2 }](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B+%5Csqrt%7B5%7D+-+2+%7D%7B+%5Csqrt%7B5%7D+%2B+2+%7D++%5Ctimes++%5Cfrac%7B+%5Csqrt%7B5%7D++-+2%7D%7B+%5Csqrt%7B5%7D+-+2+%7D+)
![= > \frac{ {( \sqrt{5} - 2)}^{2} }{ {( \sqrt{5} )}^{2} - {(2)}^{2} } = > \frac{ {( \sqrt{5} - 2)}^{2} }{ {( \sqrt{5} )}^{2} - {(2)}^{2} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+++%5Cfrac%7B+%7B%28+%5Csqrt%7B5%7D++-+2%29%7D%5E%7B2%7D+%7D%7B+%7B%28+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D++-++%7B%282%29%7D%5E%7B2%7D+%7D+)
![= > \frac{5 + 4 - 4 \sqrt{5} }{1} = > \frac{5 + 4 - 4 \sqrt{5} }{1}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5Cfrac%7B5+%2B+4+-+4+%5Csqrt%7B5%7D+%7D%7B1%7D+)
![b= 9 - 4 \sqrt{5} b= 9 - 4 \sqrt{5}](https://tex.z-dn.net/?f=+b%3D++++9++-+4+%5Csqrt%7B5%7D++)
We have to find value of ,
![= > {a}^{2} - {b}^{2} = > {a}^{2} - {b}^{2}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D+)
![= > {(9 + 4 \sqrt{5}) }^{2} - {(9 - 4 \sqrt{5} )}^{2} = > {(9 + 4 \sqrt{5}) }^{2} - {(9 - 4 \sqrt{5} )}^{2}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%7B%289+%2B+4+%5Csqrt%7B5%7D%29+%7D%5E%7B2%7D+-++%7B%289+-+4+%5Csqrt%7B5%7D+%29%7D%5E%7B2%7D++)
![= > (81 + 80 + 8 \sqrt{5} ) - (81 + 80 - 8 \sqrt{5} ) = > (81 + 80 + 8 \sqrt{5} ) - (81 + 80 - 8 \sqrt{5} )](https://tex.z-dn.net/?f=+%3D++%26gt%3B+%2881++%2B+80+%2B+8+%5Csqrt%7B5%7D+%29+-+%2881+%2B+80+-+8+%5Csqrt%7B5%7D+%29)
![= > 81 + 80 + 8 \sqrt{5} - 81 - 80 + 8 \sqrt{5} = > 81 + 80 + 8 \sqrt{5} - 81 - 80 + 8 \sqrt{5}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+81++%2B+80+%2B+8+%5Csqrt%7B5%7D++-+81++-+80+%2B+8+%5Csqrt%7B5%7D+)
![81 \: and \: - 81 \: 80 \: and \: - 80 \:get \: cancelled 81 \: and \: - 81 \: 80 \: and \: - 80 \:get \: cancelled](https://tex.z-dn.net/?f=81+%5C%3A+and+%5C%3A+-+81+%5C%3A+80+%5C%3A+and+%5C%3A++-+80+%5C%3Aget+%5C%3A+cancelled)
![= > 16 \sqrt{5} = > 16 \sqrt{5}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+16+%5Csqrt%7B5%7D+)
Hence,
![= > {a}^{2} - {b}^{2} = 16 \sqrt{5} = > {a}^{2} - {b}^{2} = 16 \sqrt{5}](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%3D+16+%5Csqrt%7B5%7D+)
______________________________
Hope it helps you!! :)
____________________________
It's given that,
We will now rationalise it ,
Now,
By rationalizing it,we get :-
We have to find value of ,
Hence,
______________________________
Hope it helps you!! :)
Similar questions